STUDI KARAKTERISTIK KIMIAWI GARAM DARI DAUN TUA TANAMAN MANGROVE (Sonneratia alba) - Sidauruk, Santhy Wisuda; Iriani, Dian; Diharmi, Andarini; Anggraini, Anggi (Marinade, 2022)
The mussel shell is a solid waste resulting from the processing of the mussel with a proportion of 51.93%, even though the shell has a high calcium content of 61.39% so there is a need for a innovation in the utilization of mussel shells into value-added products through the valorisation of freshwater mussel shells as hydroxyapatite source. This research aimed to determine the characterisation of hydroxyapatite from freshwater mussel shells. The synthesis of hydroxyapatite was carried out using the hydrothermal method at 8000C. The hydroxyapatite characteristic of freshwater mussel shell has a white color with a whiteness value of 56.89%; identified functional groups PO43-, OH-, CO32-, and CaO groups as constituents of hydroxyapatite; a high degree of crystallinity of 82.8%; 48.255% calcium; 1.474% Phosphor; and 0.009% kalium.